Discourse analysis of the New Testament writings - Scacewater, Todd A. (Fontes Press, 2020)
Matthew / David J. Clark and Todd A. Scacewater -- Mark / Robert Longacre -- Luke / Todd R. Chipman -- John / Michael Rudolph -- Acts / Jenny Read-Heimerdinger -- Romans / Aaron Sherwood -- 1 Corinthians / R. Bruce Terry -- 2 Corinthians / Fredrick J. Long -- Galatians / Stephen Levinsohn -- Ephesians / Todd A. Scacewater -- Philippians / Thomas W. Hudgins & J. Gregory Lawson -- Colossians / Todd A. Scacewater -- 1 Thessalonians / Daniel Patte -- 2 Thessalonians / Michael Aubrey -- Pastoral Epistles / Isaiah Allen -- Philemon / David L. Allen -- Hebrews / Cynthia Long Westfall -- James / William Varner -- 1 Peter / Ervin Starwalt -- 2 Peter / Christopher J. Fresch -- Johannine Epistles / Ernst Wendland -- Jude / David J. Clark -- Revelation / Stephen Pattemore.